Implementasi Profil Pelajar Pancasila Dimensi Bernalar Kritis Menggunakan Media Video Animasi - Maielfi, Dini; Nurpatri, Yeni; Zaturrahmi, Zaturrahmi (Universitas Pahlawan Tuanku Tambusai, 2024)
The issues arising in the learning process are as follows: 1) Lack of habituation to critical thinking in the teaching-learning process, 2) Students are given limited opportunities to actively participate in learning activities, 3) Insufficient supportive environment as the school does not provide enough space for students to explore and innovate, 4) Lack of support and recognition when they think critically. This results in a lack of confidence and hinders the development of their abilities. The purpose of this study is to analyze the implementation of the Pancasila Student Profile with the Critical Thinking Dimension using animated video media in Grade IV of SDN 22 Kuranji, Padang City. In the data collection process, animated video media was used. The subjects of this research are the students of Grade IV at SDN 22 Kuranji, Padang City, in the second semester of the 2023/2024 academic year. To analyze the students' needs, interviews and observations were conducted. The results of the study showed that the average critical thinking dimension score of students using animated videos was 2.62, categorized as adequate. Several efforts made by the teachers include: (1) Creating lesson plans that incorporate activities to develop students' critical thinking skills, (2) varying the use of learning media through animated videos, (3) implementing reflective-based learning tailored to the students' learning needs..